Balancing the need for investment and environmental protection : a case study of The Gambia - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2021.